Implementasi Sistem E-Procurement di PT Taman Impian Jaya Ancol Unit Sea World Ancol Jakarta Utara - Nyoman Suardhita; Aan Rahman; Rini Martiwi (LITERATUS, 2022)
The development of knowledge and technology has encouraged various large companies in Indonesia to compete with each other to advance their companies. PT Taman Impian Jaya Ancol, a unit of Sea World Ancol North Jakarta, has implemented an electoral procurement system as an application that realizes good governance. The purpose of this study was to determine the application of the E-Procurement system at PT Taman Impian Jaya Ancol Unit Sea World North Jakarta. The method used is a qualitative descriptive research method. Data collection techniques use observation, interview and documentation methods. Based on the results of this study, it can be concluded that PT Taman Impian Jaya Ancol Unit Sea World has a fairly good procurement administration procedure, with the principles of effective, efficient, competitive, transparent, fair and accountable. Electronic procurement is a web-based application system that carries out the process of all procurement of goods by utilizing the internet, by direct appointment and auction methods. The document process used by PT Taman Impian Jaya Ancol unit of Sea World Ancol North Jakarta, on the document for the implementation of procurement of goods includes a Bill of Quantity (BQ), a draft work agreement or contract, a Letter of Order (SP), a Report on Receipt of Goods (LPB), and a Minutes (BA) which are carried out regularly and archived properly. In the process of procurement of goods with an e-procurement system does not always run well, there are obstacles that occur during the implementation of procurement, namely from considering prices, not explaining complete specifications of goods, and applying the e-procurement system